(untitled) (Journal of Asian Development Studies, 2023)
The study uses logistic regression on the primary data collected through the Layyah district field survey to investigate the relationship concerning gender inequality in education and poverty. This study found that gender differences in educational attainment negatively impacts household poverty. When the proportion of females enrolled in elementary, secondary, and postsecondary education increases, the likelihood of household poverty declines. The likelihood of a home being poor is further refuted by the intensification in the female-to-male literacy ratio. The likelihood of poverty is positively correlated with the size of the household and the number of children under five but negatively correlated with the qualifications of the household head, age of the household, specialized or methodical abilities of the household head, and possession of the home.